PEMBERSIHAN DAN PERAWATAN INSTRUMENT DENTAL UNIT DALAM BIDANG KSEHATAN - I G A Raiyanti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
Utilizing dental health instrument in dental health equipment practice need a right and intensive care. One of the dental equipment is dental unit whic using in a dental health practice, every part of the dental unit need a intensive way of treating, a minimum treatment and careless of dental unit can be detriment to a process of medical patient service . In the procedure of dentat unit intensive care, may will increasing the cost, away of treating and for anew equipment